Educational, Labor-Market and Intergenerational Consequences of Poor Childhood Health - Krzysztof Karbownik; Anthony Wray (Institute of Labor Economics (IZA), 2021)
Does childhood health capital affect long-run labor market success? We address this question using inpatient hospital admission records linked to population census records. Sibling fixed effects estimates indicate that in comparison to their brothers, boys with health deficiencies were more likely to experience downward occupational mobility relative to their father's occupational rank. This decline in occupational success across generations can be decomposed into a lower likelihood of attaining white collar status and a higher likelihood of working in unskilled jobs, which translated into lower occupational wages on average. Evidence indicates that a lower school attendance rate and higher rates of disability in both childhood and adulthood are plausible mechanisms for our findings.
Keywords: I14; J62; N33; 330; childhood health capital; intergenerational inequality; occupational success